Hubungan tinggi badan terhadap jarak jauh lompatan pada saat melakukan lompat jauh siswa laki-laki SMAN Pakusari di kelas X4 - Gita Karinda; Ahmad Sulaiman; Topo Yono (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the effect of height on long jump results in the sport of long jump. The study uses a quantitative method with a correlational approach. The sample consisted of 20 students selected using purposive sampling from a population of 45 students. Data were obtained through direct measurement of height using a measuring device (CM) and jump results using a standard measuring device (M). Data analysis was performed using SPSS version 25, including Pearson's correlation test, t-test, F-test, and simple linear regression. The results showed a correlation value of r = 0.599 with a significance of 0.005 < 0.05, which means that there is a positive and significant relationship between height and long jump results. The t-value = -42.032 with Sig. = 0.000 indicates that height has a significant partial effect on long jump results, while the F-test result of 68.230.496 with Sig. = 0.000 indicates that the regression model is simultaneously significant. Thus, it can be concluded that height has a significant effect on long jump distance in the sport of long jump. Kata Kunci: Athletics, height, long jump, anthropometry